In vitro Antitubercular Activity of 3‐Deoxysappanchalcone Isolated From the Heartwood of Caesalpinia sappan Linn. (17th August 2017) - Seo, Hoonhee; Kim, Sukyung; Mahmud, Hafij Al; Islam, Md Imtiazul; Nam, Kung‐Woo; Lee, Byung‐Eui; Lee, Hanna; Cho, Myoung‐Lae; Shin, Heung‐Mook; Song, Ho‐Yeon
Abstract : Responsible for nearly 1.5 million deaths every year, the infectious disease tuberculosis remains one of the most serious challenges to global health. The emergence of multidrug‐resistant tuberculosis and, more recently, extensively drug‐resistant tuberculosis poses a significant threat in our effort to control this epidemic. New drugs are urgently needed to combat the growing threat of antimicrobial resistance. To achieve this goal, we screened approximately 500 species of medicinal plant methanol extracts and their solvent partitioned fractions for potential inhibitors of Mycobacterium tuberculosis growth. Using microdilution screening, the ethyl acetate solvent partitioned fraction from the heartwood of Caesalpinia sappan exhibited strong antitubercular activity. We isolated the active compound and identified it as 3‐deoxysappanchalcone. The extracted 3‐deoxysappanchalcone possessed activity against both drug‐susceptible and drug‐resistant strains of M. tuberculosis at MIC50 s of 3.125–12.5 μg/mL in culture broth and MIC50 s of 6.25–12.5 μg/mL inside macrophages and pneumocytes. 3‐Deoxysappanchalcone was also found to act in partial synergy with streptomycin/ethambutol against M. tuberculosis H37Rv. 3‐Deoxysappanchalcone had no cytotoxicity against the A549 cell line up to a concentration of 100 μg/mL (selectivity index > 8–32). Further studies are warranted to establish the in vivo effect and therapeutic potential of 3‐deoxysappanchalcone. Copyright © 2017 John Wiley & Sons, Ltd.